Increased Mobility of the Atrial Septum in Aortic Root Dilation: An Observational Study on Transesophageal Echocardiography - Heidemann, Altair; Dall'Oglio, Lorença; Bertoldi, Eduardo Gehling; Foppa, Murilo (Frontiers in Physiology, 2021)
Background: There is growing interest in the relationship between atrial septal anatomy and cardioembolic stroke. Anecdotal reports suggest that the enlargement of the aortic root could interfere with atrial septal mobility (ASM). We sought to investigate the association between atrial septal mobility and aortic root dilation. Methods and Findings: From all consecutive clinically requested transesophageal echocardiogram (TEE) studies performed during the study period in a single institution, we were able to review and evaluate, in 336 studies, the atrial septal mobility and anteroposterior length, aortic root diameter, and the prevalence of atrial septal aneurysm (ASA) and of patent foramen ovale (PFO). Additional variables such as left ventricular ejection fraction, left atrial diameter, diastolic dysfunction, age, sex, weight, height, previous stroke, atrial fibrillation and TEE indication were extracted from patient medical records and echocardiographic clinical reports. In 336 patients, we found a mean ASM of 3.4 mm, ranging from 0 to 21 mm; 15% had ASA, and 14% had PFO. There was a 1.0 mm increase in ASM for every 10 mm increase in aortic root diameter adjusted for age, sex, weight, height, ejection fraction and left atrial size (B=0.1; p=0.04). Aortic diameter was not associated to a smaller septal length (B=0.03; p=0.7). Conclusions: An increased motion of atrial septum can occur in association with aortic dilation. These findings deserve attention for the relevance of aortic root anatomy in future studies of atrial septal characteristics and embolic stroke risk.